A randomised controlled trial on hypolipidemic effects of Nigella Sativa seeds powder in menopausal women - Mohamad Ibrahim, Ramlah; Hamdan, Nurul Syima; Mahmud, Rozi; Imam, Mustapha Umar; Mohd Saini, Suraini; Abdul Rashid, Saiful Nizam; Abd Ghafar, Siti Aisyah; Abd Latiff, Latiffah; Ismail, Maznah (BioMed Central, 2014)
Background: The risk of cardiovascular diseases (CVD) is increased tremendously among menopausal women, and there is an increasing demand for alternative therapies for managing factors like dyslipidemia that contribute to CVD development. Methods: In this study, Nigella sativa was evaluated for its hypolipidemic effects among menopausal women. In a randomised trial, hyperlipidemic menopausal women were assigned to treatment (n = 19) or placebo groups (n = 18), and given N. sativa or placebo for two months after their informed consents were sought. At baseline, blood samples were taken and at one month intervals thereafter until one month after the end of the study. Results: The results showed that N. sativa significantly improved lipid profiles of menopausal women (decreased total cholesterol, low density lipoprotein cholesterol and triglyceride, and increased high density lipoprotein cholesterol) more than the placebo treatment over 2 months of intervention. One month after cessation of treatment, the lipid profiles in the N. sativa-treated group tended to change towards the pretreatment levels. Conclusions: N. sativa is thought to have multiple mechanisms of action and is cost-effective. Therefore, it could be used by menopausal women to remedy hypercholesterolemia, with likely more benefits than with single pharmacological agents that may cause side effects. The use of N. sativa as an alternative therapy for hypercholesterolemia could have profound impact on the management of CVD among menopausal women especially in countries where it is readily available.